The technique and tactics analysis of Fan Zhendong in the quarterfinal of the 2015 Kuwait Open - Jiao, T.; Huang, W. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
1. Purpose: Born in 1997, Chinese table tennis player Fan Zhendong has improved greatly in techniques and tactics in the past two years and has stood out quickly among many young players with his advanced techniques. Growing with such astonishing speed, Fan has won the men`s team champions in 2014 Tokyo World Table Tennis Championships, 2014 Inchon Asian Games and the men`s singles gold medal in 2014 Nanjing Youth Olympic Games. This thesis studies Fan`s performance in 2015 Kuwait Open in detail and hopes to provide scientific basis to his technical and tactical training in the future. 2. Methods: This thesis studies 1 important matches of Fan in 2015 Kuwait Open: quarterfinal match Fan Zhendong VS ZHUANG Zhiyuan (score 4:2) The thesis analyses his application in techniques and tactics through counting scoring rate, using rate and related score trend of the first and third strokes, the second and forth strokes and sustained rally. 3. Results and Conclusions (1) Fan could use his forehand counter spin serve to score or make chances for the third attack. His third backhand attack is fast with high spin, which helps him get a lot of points in the match. (2) Receive and attack is his best performance part in this match. He repeatedly uses the speed and high side spin of the backhand twist over the table to bring some trouble for Chuang`s return. In the whole match, Fan`s forth stroke with high speed and spin is stronger than Chuang. (3) The confrontation is Fan`s shortcoming. In the confrontation, his speed of backhand stroke is restraint by his opponent, which causes more faults in the backhand and sideways drives.